2012
DOI: 10.1371/journal.pone.0044409
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of Prebiotic Uptake and Catabolism by Lactobacillus acidophilus NCFM

Abstract: The human gastrointestinal tract can be positively modulated by dietary supplementation of probiotic bacteria in combination with prebiotic carbohydrates. Here differential transcriptomics and functional genomics were used to identify genes in Lactobacillus acidophilus NCFM involved in the uptake and catabolism of 11 potential prebiotic compounds consisting of α- and β- linked galactosides and glucosides. These oligosaccharides induced genes encoding phosphoenolpyruvate-dependent sugar phosphotransferase syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 56 publications
4
54
0
4
Order By: Relevance
“…L. acidophilus NCFM is one of the best-studied gut bacteria, which is ascribed health benefits and used as a commercial probiotic (34)(35)(36)(37). The commercial and physiological relevance of L. acidophilus NCFM has spurred wide interest in the saccharide uptake and catabolism machinery of this organism to identify efficiently utilized glycans with potential as prebiotics (25,38,39). A few intracellular carbohydrate-active enzymes (CAZymes) from L. acidophilus NCFM have been characterized, including those active on maltose (26) and ␣-1,6-linked isomalto-oligosaccharides (24).…”
Section: Discussionmentioning
confidence: 99%
“…L. acidophilus NCFM is one of the best-studied gut bacteria, which is ascribed health benefits and used as a commercial probiotic (34)(35)(36)(37). The commercial and physiological relevance of L. acidophilus NCFM has spurred wide interest in the saccharide uptake and catabolism machinery of this organism to identify efficiently utilized glycans with potential as prebiotics (25,38,39). A few intracellular carbohydrate-active enzymes (CAZymes) from L. acidophilus NCFM have been characterized, including those active on maltose (26) and ␣-1,6-linked isomalto-oligosaccharides (24).…”
Section: Discussionmentioning
confidence: 99%
“…The increased transcription of genes encoding "hypothetical proteins" and an ABC transporter gene may be involved in the phenomenon. A recent analysis of the transcriptional response of Lactobacillus acidophilus to growth on stachyose (a tetrasaccharide) showed increased transcription of ABC transporters (25). Crystal structure studies have shown ABC transporters binding tetrasaccharide with the strongest interactions at the nonreducing end of the carbohydrate (26).…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the influence of environmental conditions on genome-wide gene expression levels, wholegenome DNA microarrays have often been used to survey the gene expression patterns of strains in the presence and absence of oligosaccharides (2,(5)(6)(7)(8). On the basis of in silico analysis of the Lactobacillus acidophilus NCFM genome sequence, Barrangou et al (2) identified a multiple-sugar metabolism (msm) operon that was involved in the metabolism of FOS.…”
mentioning
confidence: 99%